Sovereign credit ratings, market volatility, and financial gains - António Afonso; Pedro Gomes; Abderrahim Taamouti (European Central Bank (ECB), 2014)
The reaction of EU bond and equity market volatilities to sovereign rating announcements (Standard & Poor's, Moody's, and Fitch) is investigated using a panel of daily stock market and sovereign bond returns. The parametric volatilities are filtered using EGARCH specifications. The estimation results show that upgrades do not have significant effects on volatility, but downgrades increase stock and bond market volatility. Contagion is present, with sovereign rating announcements creating interdependence among European financial markets with upgrades (downgrades) in one country leading to a decrease (increase) in volatility in other countries. The empirical results show also a financial gain and risk (value-at-risk) reduction for portfolio returns when taking into account sovereign credit ratings' information for volatility modelling, with financial gains decreasing with higher risk aversion.
Keywords: C22; C23; E44; G11; G15; H30; 330; EGARCH; financial gain; optimal portfolio; risk management; sovereign ratings; stock market returns; value-at-risk; volatility; yields